The Role of Molecular Systematics in Microbiological Research and Public Health: A Systematic Review - Ablola, Ferissa; Bautista, Ana Liza; Migalang, Gilden Maecah; Christa Jesusa Naval (International Journal of Applied Biology, 2023)
The robust development of molecular biology and bioinformatics in recent years has given researchers strong tools for addressing long-standing issues in all branches of biology. The process of reconstructing phylogenetic relationships using molecular data is known as "molecular systematics." In this systematic review, the utilization of molecular techniques in systematics were described in the two fields of microbiological research and public health. A total of twenty articles were included in this study, which showcased nine unique molecular methods with distinct advantages and limitations of use. It was revealed that the aim of most articles under the biological researches is to identify a certain group of microorganisms while, the determination of phylogenetic relationship and outbreak investigation were the main goals of public health utilization of molecular systematics techniques.